Detection and Monitoring of Regulatory Immune Cells Following Their Adoptive Transfer in Organ Transplantation - Tran, Lillian M.; Thomson, Angus W. (Frontiers in Immunology, 2020)
Application of cell-based immunotherapy in organ transplantation to minimize the burden of immunosuppressive medication and promote allograft tolerance has expanded significantly over the past decade. Adoptively transferred regulatory immune cells prolong allograft survival and transplant tolerance in pre-clinical models. Many cell products are currently under investigation in early phase human clinical trials designed to assess feasibility and safety. Despite rapid advances in manufacturing practices, defining the appropriate protocol that will optimize in vivo conditions for tolerance induction remains a major challenge and depends heavily on understanding the fate, biodistribution, functional stability and longevity of the cell product after administration. This review focuses on in vivo detection and monitoring of various regulatory immune cell types administered for allograft tolerance induction in both pre-clinical animal models and early human clinical trials. We discuss the current status of various non-invasive methods for tracking regulatory cell products in the context of organ transplantation and implications for enhanced understanding of the therapeutic potential of cell-based therapy in the broad context of control of immune-mediated inflammatory disorders.